Erosion Rate of Lateral Slope Deposit Under the Effects of Different Influencing Factors - Ge, Yonggang; Guo, Xiaojun; Zhan, Meiqiang; Yan, Hua (Frontiers in Earth Science, 2021)
Lateral slope deposits along a channel represent an important source of material for initiation and development of debris flows/floods that are typically observed in many headwater tributaries. This study found that the failure process of such a deposit reflects combined interaction between external hydrodynamic factors (inflow discharge and channel slope) and internal factors (compactness and fine particle content). The erosion process comprises two stages: runoff erosion toward the toe of the deposit body and soil failure owing to gravity. Spatially, the erosion rate is distributed unevenly across the deposit; the highest value occurs at the section close to the middle of the deposit, on the upstream face. Temporally, the erosion rate decreases exponentially. Overall, the average erosion rate decreases (increases) with bulk density (inflow discharge and channel slope). However, a slope of 7 is a threshold at which the tendency of the erosion rate in relation to the fine particle content differs. In comparison with the other three influencing factors, the effect of the fine particle content is much smaller. Although the bulk density of the deposit imposes the most significant effect, it is of the same order as that of both inflow discharge and channel slope. As the failure process can be summarized as repeated runoff scouring of the toe of the deposit, deposit failure, and entrainment of the failure body by runoff, we proposed a calculation method for the total time required for a complete lateral erosion process, and validation of the calculation suggested its reasonability. The findings of this study enhance the understanding of the mechanism of lateral soil deposit failure, which could help improve runoff-induced debris flood forecasting in headwater regions of mountainous catchments.